VCDT: the virtual classroom debate tutorial approach / Azlyn Ahmad Zawawi ... [et al.] - Ahmad Zawawi, Azlyn; Ismail, Junaida; Mohd Hakimi, Irwana Nooridayu; Rusli, Noorayuni; Azizan, Intan Syahriza (2021)
Debate has been commonly used as a medium of learning in the classroom at the secondary and tertiary levels. A lot has changed in the past years, causing learning approaches to shift from conventional face-to-face practices to a more modern and virtual medium of learning. Virtual learning can be dull, unexciting, and monotonous if not managed well by the instructors. Therefore, the VCDT Approach is introduced to foster two-way participation in online tutorial sessions. The practice of virtual classroom debate develops self-confidence, critical thinking, analytical capabilities, communication skills, and teamwork, even in the new norms. Although various studies involving debate have been done in the context of learning the second language, psychology, philosophy, and pure science, studies that focus on the impact of classroom debate are still scarce. The VCDT Approach promotes a brilliant way of online discussion in which students are encouraged to speak spontaneously on chosen subject matters. A properly executed debate exercise can allow students to exert fresh ideas and develop reasoning skills that can improve their communication skills, which could impact their academic performance. Debate activities encourage the development of various abilities needed by students such as effective written and oral communication, critical thinking, working in a collaborative environment, civic awareness, and active class participation. Nature of debate activities helps sharpen rhetorical skills in a fast-paced virtual environment, enriching their ability to solve problems and engage in autonomous learning. Therefore, in VCDT exercises, students can practice generating ideas under pressure while learning key ideas in a given time.